Australia : Basel Core Principles for Effective Banking Supervision-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2012)
Australia has a very high level of compliance with the Basel Core Principles for Effective Banking Supervision (BCPs). The Australian banking system was more sheltered than a number of other countries and weathered the Global Financial Crisis relatively well. This was in part due to relative concentration of the system on a well performing domestic economy, but also due to a material contribution from a well-developed regulatory and supervisory structure. Notable strengths of the Australian supervisory approach rest in its strong risk analysis and on the focus of the responsibility of the Board. The Australian banking system however, is still vulnerable to continuing aftershocks of the financial crisis not least as banks? funding profiles could be a conduit of instability.